TRADITION OF TYPES IN THE WORK OF ABDULLAH SHERq (Scientific journal of the Fergana State University, 2024)
Anthropology, imagery, the importance of invention, the typicality of depiction, and the distinctive role of language are very important aspects of the specificity of literary art. Unlike simple reflections, the image created by the artist reflects reality in an artistic and emotional manner.The ability to typify and individualize life material is the most essential condition for creating an artistic image. In an artistic image, we encounter not the general characteristics of social types or events, but rather the specific characteristics that are distinctive of their concrete representative, their individual appearance. Depending on the role and function of the image in the work, it is expressed in literature with terms such as character, main image, secondary image, persona, and type. The first characteristic of an artistic image is its vividness, clarity, and richness in distinctive features, which determine the emotional impact of art and literature on people. The second distinctive feature of the image is that it embodies both specific, unique, and at the same time, general, typical traits.